Therapeutic Drug Monitoring of Antibiotics Is Needed in the Treatment of Sepsis - G. P. Plotnikov; A. N. Kudryavtsev; A. A. Kleuzovich; A. G. Chizhov; A. A. Ponomarev; S. S. Larin; E. A. Litvin; L. A. Anastasevich (Вестник анестезиологии и реаниматологии)
The article presents the results of a prospective one-center observational clinical study.The level of therapeutic drug monitoring antibiotics was studied in patients with sepsis.The objective: to assess the impact of pharmacokinetics and pharmacodynamics parameters of the main classes of antibacterial drugs using specific indices to improve the effectiveness of ongoing antimicrobial therapy in patients with sepsis asscoaited with the infectious process with pan-resistant nosocomial microflora.Subjects and Methods. A total of 8 patients with sepsis meetiing the criteria of Sepsis-3 were included. Carbapenems, oxazolidinones, and aminoglycosides were used in the treatment. Concentrations of drugs in blood plasma were studied by high-performance liquid chromatography with mass spectrometry. Analysis of the effectiveness of treatment was performed on the third day of therapy.Results. The T > MIC index reached 40% of the time interval between the two administrations for MIC for Pseudomonas aeruginosa in only two cases for group II carbapenems.In both cases, high peak concentrations of the drug (19.5 and 35.4 mg/L, respectively) were observed, a low static volume of antibiotic distribution (0.06 l/kg and 0,09 l/kg) and reduced total clearance of the drug (7.18 and 4.11 ml/hr) were noted. The peak concentration of amikacin was low (3.35 mg/l), while the time to achieve it and the level of static volume distribution (356.5 liters) increased. The peak concentration of linezolid was reduced in all observations and amounted to 4.04 and 3.35 mg/l. The time of its achievement was increased (3.27 and 6.6 hours), the ratio of AUC/MIC was low and made 76.8 and 59.2.The resolution of organ dysfunction and reduction of manifestations of infectious intoxication were noted only in three patients on the third day of observation.Conclusion. Static pharmacokinetic/pharmacodynamic criteria may serve as a guideline for antimicrobial therapy.Limitations in changing the tactics of antimicrobial therapy based on the use instruction nevertheless allow optimizing treatment by controlling the volume of distribution of the drug, presence of renal or hepatic insufficiency that, however, does not guarantee treatment success. The volume of therapeutic drug monitoring of antibiotics sufficient for compilation of static pharmakinetic models, does not meet the requirements of modern intensive care.